2022
DOI: 10.3390/cancers14092219
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Plasma Tumor DNA (ctDNA) Correlates with PSA Kinetics in Metastatic Castration-Resistant Prostate Cancer (mCRPC) Treated with Abiraterone or Enzalutamide

Abstract: Background: Baseline high circulating tumor DNA (ctDNA) fraction in plasma and androgen receptor (AR) copy number (CN) gain identify mCRPC patients with worse outcomes. This study aimed to assess if ctDNA associates with PSA kinetics. Methods: In this prospective biomarker study, we evaluate ctDNA fraction and AR CN from plasma samples. We divided patients into high and low ctDNA level and in AR gain and AR normal. Results: 220 baseline samples were collected from mCRPC treated with abiraterone (n = 140) or en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…AR amplification is an important mechanism of castration resistance and an adverse prognostic factor occurring in 40% of CRPC but almost never in CSPC [ 42 ]. We detected AR amplifications in 31% of mCRPC patients, in agreement with previous reports [ 43 ]. Due to the small size of our panel, gene losses could not be investigated, which is one of our assay’s limitations.…”
Section: Discussionsupporting
confidence: 92%
“…AR amplification is an important mechanism of castration resistance and an adverse prognostic factor occurring in 40% of CRPC but almost never in CSPC [ 42 ]. We detected AR amplifications in 31% of mCRPC patients, in agreement with previous reports [ 43 ]. Due to the small size of our panel, gene losses could not be investigated, which is one of our assay’s limitations.…”
Section: Discussionsupporting
confidence: 92%
“…However, even when accounting for these poor-risk clinical features, higher pretreatment cfDNA concentration and ctDNA% independently predicts shorter progression-free and overall survival in patients commencing contemporaneous systemic therapies. These associations are evident in men receiving next-generation ARPIs such as abiraterone and enzalutamide (5,(40)(41)(42)(43)(44)(45), as well as taxane cytotoxic therapies docetaxel and cabazitaxel (16,39,46,47). Less well understood is the precise relationship between these metrics and life expectancy.…”
Section: Prognostic Value Of Ctdna%mentioning
confidence: 99%
“…Several studies have shown an association between elevated baseline cfDNA concentrations and ctDNA% values (the proportion of ctDNA in total cfDNA) and reduced PFS and OS in mCRPC patients treated with ARSI (e.g., enzalutamide, abiraterone) and chemotherapy (e.g., docetaxel, cabazitaxel) [ 49 51 ]. Furthermore, it has been reported that patients with mCRPC patients who exhibit persistent ctDNA levels after four weeks of initial treatment with ARSI are at a higher risk of developing acquired resistance within six months of commencing treatment, resulting in shorter PFS and OS outcomes [ 51 ].…”
Section: Introductionmentioning
confidence: 99%